The Health Effects of Aluminum Exposure - Klotz, Katrin; Weistenhöfer, Wobbeke; Neff, Frauke; Hartwig, Andrea; van Thriel, Christoph; Drexler, Hans (Deutsches Ärzteblatt international, 2017)
Aluminum is regularly taken up with the daily diet. It is also used in antiperspirants, as an adjuvant for vaccination, and in desensitization procedures. In this review, we present the scientifically documented harmful effects of aluminum on health and the threshold values associated with them. This review is based on publications retrieved by a selective search of the PubMed and SCOPUS databases on the topic of aluminum in connection with neurotoxicity, Alzheimer's disease, and breast cancer, as well as on the authors' personal experience in occupational and environmental medicine. The reference values for the internal aluminum load (<15 μg/L in urine, <5 μg/L in serum) are especially likely to be exceeded in persons with occupational exposure. The biological tolerance value for occupational exposure is 50 μg of aluminum per gram of creatinine in the urine. For aluminum welders and workers in the aluminum industry, declining performance in neuropsychological tests (attention, learning, memory) has been found only with aluminum concentrations exceeding 100 μg/g creatinine in the urine; manifest encephalopathy with dementia was not found. Elevated aluminum content has been found in the brains of persons with Alzheimer's disease. It remains unclear whether this is a cause or an effect of the disease. There is conflicting evidence on carcinogenicity. The contention that the use of aluminum-containing antiperspirants promotes breast cancer is not supported by consistent scientific data. The internal aluminum load is measured in terms of the concentration of aluminum in urine and blood. Keeping these concentrations below the tolerance values prevents the development of manifest and subclinical signs of aluminum toxicity. Large-scale epidemiologic studies of the relationship between aluminum-containing antiperspirants and the risk of breast cancer would be desirable.